Comparative study on conventional and microalgae-based air purifiers: Paving the way for sustainable green spaces - Kumar, Pradeep; Arora, Kanika; Chanana, Ishita; Kulshreshtha, Sourabh; Thakur, Vikram; Choi, Kwon Young (Journal of Environmental Chemical Engineering, 2023)
Every year, anthropogenic air pollution causes 7 million people to die due to various respiratory-related diseases, with indoor air quality having a significant impact on people's health. With the emergence of the COVID-19 pandemic, clean air, and good indoor air quality have become of paramount importance. In light of the high levels of pollution that have reached unprecedented levels, the only effective solution is to implement air purifying technology. However, identifying one sustainable purifier that can perform efficiently in changing environmental conditions with a low environmental impact and is economically viable is a daunting task. This state-of-the-art review will elucidate about all the conventional physio-chemical technologies and their comprehensive comparison with advancing biotechnology-based solutions considering all the important parameters. The techno-economic and life cycle assessment of the air purifiers have been evaluated to give the situational concept of their position in air purification market, so as to understand the competition level between the two. Microalgal Air Purification Technology (MAPT) driven air purifiers are emerging as a sustainable alternative to the conventional ones with their diversity of pollutant control and versatility in applications of the produced biomass. Conversely, physio-chemical technology is more in demand on the grounds of easy availability and affordable price. Thus, this critical analysis highlights the advantages and disadvantages of each method with real-time examples of established and emerging ventures in green air purifier market.
Keywords: Anthropogenic air pollution; Chemical technologies; Comparatives studies; Conventional air purifier; Green spaces; Indoor air quality; Life cycle assessment, microalgal air purifier; Micro-algae; Physio-chemical; Techno-economics; Air pollution; Conventional air purifier; Life cycle assessment, microalgal air purifiers; Sustainability; Techno-economic